Correction to: Gender-affirming hormonal therapy induces a gender-concordant fecal metagenome transition in transgender individuals (BMC Medicine, (2024), 22, 1, (346), 10.1186/s12916-024-03548-z) - Liwinski, Timur; Auer, Matthias K.; Schröder, Johanna; Pieknik, Ina; Casar, Christian; Schwinge, Dorothee; Henze, Lara; Stalla, Günter K.; Lang, Undine E.; von Klitzing, Alina; Briken, Peer; Hildebrandt, Thomas; et al. (BMC Medicine, 2025)
After publication of this article [1], it came to the attention of the authors that the public accession number to the original next-generation sequencing dataset was not provided. The authors have updated the article to include the following information: The next-generation sequencing data set associated with this study is available in the European Nucleotide Archive (ENA) under the accession number ERP169623, project PRJEB86263. The data can be accessed at https://www.ebi.ac.uk/ena/browser/view/PRJEB86263.
CRIS-Team Scopus Importer:2025-06-13